덧댐굴절력 +1.5디옵터 굴절성 비구면 이중초점인공수정체의 임상결과 - 전성연(Sung Yeon Jun); 조영주(Young Joo Cho); 조범진(Beom Jin Cho) (Daihan angwa haghoi jabji, 2021)
목적: 백내장수술시 굴절성 비구면 이중초점인공수정체 Lentis®Comfort (LS-313MF15, Oculentis)를 삽입한 환자들의 술 후 3개월 임상성적을 알아보고자 한다. 대상과 방법: 굴절성 비구면 이중초점인공수정체 Lentis®Comfort를 삽입한 51명 82안을 대상으로 술 후 1개월, 3개월에 나안 및 최대교정 원거리, 중간거리, 근거리 시력, 굴절오차 및 술 후 3개월의 탈초점곡선, 대비감도검사, 설문 조사를 이용한 만족도를 조사하였다. 결과: 수술 후 3개월째 평균 구면렌즈 대응치는 -0.12 ± 0.21 D였으며, 원거리 나안시력(LogMAR), 중간거리 80 cm 나안시력, 근거리 40 cm 나안시력(LogMAR)은 각각 0.02 ± 0.03, 0.13 ± 0.07, 0.42 ± 0.10이었다. 수술 후 3개월째에 시행한 탈초점곡선의 원거리와 중간거리 사이에서 0.2 (LogMAR) 이상의 시력이 관찰되었다. 대비감도검사에서는 명조건과 암조건에서 정상 시력 인구의 90% 범주에 속하는 평균 대비감도 결과값이 확인되었고, 71.8%가 만족 또는 매우 만족하며 약 20%가 이상빛감각이 있다고 설문 조사에 응답하였다. 결론: 백내장 환자에서 굴절성 비구면 이중초점인공수정체(Lentis®Comfort, LS313-MF15)의 삽입 후 3개월 경과 관찰까지 수술 전보다 개선된 원거리, 중간거리 시력이 유지되었고, 객관적 및 주관적 시력의 질 평가에서도 다른 인공수정체와 견줄 수 있는 시력의 질이 확인되었다. Purpose: We evaluated the 3-month, postoperative clinical outcomes of patients implanted with refractive, aspheric, bifocal, Lentis Comfort (LS313-MF15, Oculentis) intraocular lenses (IOLs). Methods: Eighty-two eyes of 51 cataract patients underwent phacoemulsification and were implanted with Lentis Comfort IOLs. The uncorrected distant visual acuity (UCDVA), the 80-cm uncorrected intermediate visual acuity (UCIVA), the 40-cm uncorrected near visual acuity (UCNVA), and refractive values were evaluated 1 and 3 months postoperatively. At the latter time, defocus curves were drawn, contrast sensitivity tested, and satisfaction surveyed. Results: At the 3-month postoperative follow-up, the mean spherical equivalent was -0.12 ± 0.21 D; and the mean LogMAR UCDVA, 80-cm UCIVA, and 40-cm UCNVA were 0.02 ± 0.03, 0.13 ± 0.07, and 0.42 ± 0.10 respectively. The defocus curves revealed visual acuities in excess of 0.2 LogMAR at points between the distant and intermediate targets. The mean contrast sensitivity fell in the range of 90% of a normal population under both photopic and mesopic conditions. In terms of satisfaction, 71.8% of patients were satisfied or very satisfied, but about 20% reported dysphotopsia. Conclusions: Implantation of the refractive, aspheric, bifocal, intraocular, Lentis Comfort in patients with cataracts improved both the distant and intermediate visual acuities by 3 months after surgery and the visual quality was comparable to that afforded by other IOLs both objectively and subjectively. KCI Citation Count: 0